Effect of Oil Content on Flavour Release: Static Equilibrium Headspace above Milk-Based Emulsions - ZA Shojaei; RST Linforth; AJ Taylor (Tehran University of Medical Sciences, 2005)
Static headspace measurements were performed using Atmospheric Pressure Chemical Ionisation- Mass Spectrometer (APCI-MS) to determine volatile partitioning from a series of milk-based emulsions. The 20 aroma compounds studied exhibited a broad range of hydrophobicity/ hydrophilicity in model emulsions. Experimental method was done using 6 samples with different lipid contents (0.002-0.102 g/mL). The results showed that there were three groups of volatile compounds due to their lipophilicities; the least, intermediate and most lipophilic volatile compounds. Overall, the release of lipophilic molecules was so dependent of the fat content of the matrix which opposed to the release of the very hydrophilic compounds.